Conodont zonation of Lower Triassic strata in Slovenia - Kolar-Jurkovšek, Tea; Jurkovšek, Bogdan (Geologija, 2015)
The paper presents the results of a conodont study carried out in the Triassic strata in the area of the Slovenian part of the Southern Alps, External Dinarides and the Transition region between the External and Internal Dinarides. The following conodont zones have been distinguished: Hindeodus praeparvus Z., H. parvus Z., Isarcicella lobata Z., I. staeschei -1, isarcica Z., H. postparvus Z., Hadrodontina aequabilis Z., Ha. anceps Z., Eurygnathodus costatus Z., Neospathodusplanus Z., N. robustus Z., Platyvillosus comiger Z., Pl. regularis Z., Pachycladina obliqua Z., Foliella gardenae Z., Triassospathodus hungaricus Z., T. symmetricus Z., N. robustispinus - T. homeri Z. and T. triangularis Z. The introduced conodont zonation spans from the Induan, including the Permian-Triassic boundary interval to the late Olenekian and is valid for the shallow shelf environments of western Tethys.